Interpersonal Skills: An Analysis According to the Perspective of al-Quran and al-Sunnah - Nik Yusri Musa; Marwan Ismail; Muhammad Hafizuddin (Journal of Social Transformation and Regional Development, 2021)
This article is a study on the concept of individual skills (Interpersonal skills) according to the perspective of the Qur'an and Sunnah. Writing and research related to individual skills according to Islamic perspective are hard to find, most of the writing-related to it is from Western scholars and of course according to their perspective. Such a situation occurs in most fields of knowledge that are professional, it does not happen in the field or discipline of knowledge that is core. Accordingly, it is not something that is difficult to interpret because this field of Interpersonal skills has been developed and processed as a professional field by Western scholars. The situation is in line with the development of secular Western civilization based on the separation of knowledge from religion and morality from life. This writing is based on qualitative methodology through observational and research approach which is later through the method of formulation of the nusus al-Quran and al-Sunnah. The texts will be analyzed to formulate key themes related to the concept of individual skills.